Different Modes of Regulation of the Expression of Dextransucrase in Leuconostoc lactis AV1n and Lactobacillus sakei MN1 - Besrour-Aouam, Norhane; Mohedano, Maria Luz; Fhoula, Imene; Zarour, Kenza; Najjari, Afef; Aznar, Rosa; Prieto, Alicia; Ouzari, Hadda-Imene; López, Paloma (Frontiers in Microbiology, 2019)
Leuconostoc lactis AV1 strain isolated from a Tunisian avocado was characterized as a dextran producer. The promoter PdsrLL and the dsrLL gene encoding the DsrLL dextransucrase responsible for the dextran synthesis were transcriptionally fused to the mCherry coding gene generating the pRCR20 plasmid. Upon plasmid transfer, both AV1n and the dextran non-producing Leuconostoc mesenteroides CM70 became red due to expression of the mCherry from the PdsrLL-dsr-mrfp transcriptional fusion. Characterization of the polymers present in cultures supernatants revealed that the DsrLL encoded from pRCR20 in the recombinant bacteria was able to synthesize dextran. The production of dextran by the DsrLL in AV1n increased in response to low temperature, reaching 10-fold higher levels at 20 ºC than at 37 ºC (4.15 g/L versus 0.41 g/L). To analyze if this stress response includes activation at the transcriptional level and if it was only restricted to Leuconostoc, AV1n was transformed with plasmids carrying either the PdsrLL-mrfp fusion or the PdsrLS of Lactobacillus sakei MN1 fused to the mrfp gene, and the influence of temperature and carbon source on expression from the Dsr promoters was monitored by measurement of the mCherry levels. The overall expression analysis confirmed an induction of expression from PdsrLL upon growth at low temperature (20 ºC versus 30 ºC and 37 ºC) the presence of all sugars tested (sucrose, glucose, maltose and fructose). In addition, in the presence of sucrose, the substrate of Dsr, also resulted in activation of expression from PdsrLL. A different behavior was detected, when expression from PdsrLS was evaluated. Similar levels of fluorescence were observed irrespectively of the carbon source or temperature, besides a sequential decrease at 30 ºC and 20 ºC, when sucrose was present in the growth medium. In conclusion, the two types of regulation of expression of Dsr presented here revealed two different mechanisms for environmental adaptation of Leuconostoc and Lactobacillus that could be exploited for industrial applications.